Impacto sanitario de los preparados magistrales y oficinales en el ámbito de la ciudad de buenos aires, republica argentina durante el año 2007” - Arguedas Deza, Frank Yudel (2008)
In the present study there decided the sanitary impact of compounding pharmaceutical and oficinales in the area of the city of Buenos Aires, republic Argentina in the year 2007. For which one worked with records and surveys it brings over of the production of compounding pharmaceutical recipes. One thought that from 1901-1945 one 24,29% it initiated its production and of 1945-2007 one 75,71%. From 1999 to 2007 one thought that 75,71 % of drugstores is accredited. A 76,92% of drugstores its active principles, exicipients and packages to establishments certified to national level guaranteeing the quality of compounding pharmaceutical and oficinales. A 94,29% offices of drugstore have some semiautomatic equipment. Besides there decided that in the drugstores is elaborated from injectable (25,71 %) up to powders (45,71 %). And the most offered medicines they are: the Anorexigénicos 80 % and Antihypertensive 80 %. The compounding pharmaceutical and oficinales that mainly are elaborated sound: mazindol 2mg 8,97 %; alprazolam 1mg 7,59 %; enalapril 10mg 6,67 %. In conclusion the coumpounding farmaceutical and oficinales they have a positive impact in the city of Buenos Aires, republic Argentina during the year 2007